Development, validation and clinical application of Pelvic Lymphadenectomy Assessment and Completion Evaluation: intraoperative assessment of lymph node dissection after robot‐assisted radical cystectomy for bladder cancer. (18th January 2017) - Hussein, Ahmed A.; Hinata, Nobuyuki; Dibaj, Shiva; May, Paul R.; Kozlowski, Justen D.; Abol‐Enein, Hassan; Abaza, Ronney; Eun, Daniel; Khan, Mohamed S.; Mohler, James L.; Agarwal, Piyush; Pohar, Kamal; et al.
Abstract : Objectives: To develop a scoring tool, Pelvic Lymphadenectomy Appropriateness and Completion Evaluation (PLACE), to assess the intraoperative completeness and appropriateness of pelvic lymph node dissection (PLND) following robot‐assisted radical cystectomy (RARC). Patients, Subjects and Methods: A panel of 11 open and robotic surgeons developed the content and structure of PLACE. The PLND template was divided into three zones. In all, 21 de‐identified videos of bilateral robot‐assisted PLNDs were assessed by the 11 experts using PLACE to determine inter‐rater reliability. Lymph node (LN) clearance was defined as the proportion of cleared LNs from all PLACE zones. We investigated the correlation between LN clearance and LN count. Then, we compared the LN count of 18 prospective PLNDs using PLACE with our retrospective series performed using the extended template (No PLACE). Results: A significant reliability was achieved for all PLACE zones among the 11 raters for the 21 bilateral PLND videos. The median (interquartile range) for LN clearance was 468 (431–545). There was a significant positive correlation between LN clearance and LN count ( R 2 = 0.70, P < 0.01). The PLACE group yielded similar LN counts when compared to the No PLACE group. Conclusions: Pelvic Lymphadenectomy Appropriateness and Completion Evaluation is a structured intraoperative scoring system that can be used intraoperatively to measure and quantify PLND for quality control and to facilitate training during RARC.